2020
DOI: 10.3390/antibiotics9090537
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Stilbene–Coumarin Derivatives and Antifungal Screening of Monotes kerstingii-Specialized Metabolites Against Fusarium oxysporum

Abstract: Fusarium is one of the most toxigenic phytopathogens causing diseases and reduced agricultural productivity worldwide. Current chemical fungicides exhibit toxicity against non-target organisms, triggering negative environmental impact, and are a danger to consumers. In order to explore the chemical diversity of plants for potential antifungal applications, crude extract and fractions from Monotes kerstingii were screened for their activity against two multi-resistant Fusarium oxysporum strains: Fo32931 and Fo4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Nonetheless, they are not the most studied group of compounds found in A. altissima and require further investigation [9]. Coumarins, and especially prenylated coumarins, have already been studied and have antibacterial [10,11], antifungal [12], antileishmanial [13], anticancer [14], anti-inflammatory and antiviral [15] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, they are not the most studied group of compounds found in A. altissima and require further investigation [9]. Coumarins, and especially prenylated coumarins, have already been studied and have antibacterial [10,11], antifungal [12], antileishmanial [13], anticancer [14], anti-inflammatory and antiviral [15] activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phenolic compounds, including components of essential oils, exhibit a variety of antimicrobial properties [ 11 , 12 ]. Furthermore, it has been demonstrated that the efficacy of antimicrobial compounds could be enhanced through synthetic modification [ 13 ]. To this end, we report a convenient method to develop QSAR models based on topological descriptors and density functional theory derived molecular orbital properties that is capable of predicting antifungal and antibiotic activity against Aspergillus species, Penicillium species, Gram-positive Staphylococcus aureus and Bacillus subtilis , and Gram-negative Escherichia coli and Pseudomonas aeruginosa [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin (2H-chromen-2-one) is the part of many compounds with antimicrobial and antifungal activity [1][2][3][4]. The recent studies show that 2H-chromen-2ones can reduce the bacterial biofilm formation for some strains of bacteria as the result making them less antibiotic resistant [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%